Molecular characterization of antigen-peptide pulsed dendritic cells: immature dendritic cells develop a distinct molecular profile when pulsed with antigen peptide. - Amy X Yang; Numju Chong; Yufei Jiang; Jennifer Catalano; Raj K Puri; Samir N Khleif (PLoS ONE, 2014)
As dendritic cells (DCs) are the most potent professional antigen-presenting cells, they are being tested as cancer vaccines for immunotherapy of established cancers. Although numerous studies have characterized DCs by their phenotype and function, few have identified potential molecular markers of antigen presentation prior to vaccination of host. In this study we generated pre-immature DC (piDC), immature DC (iDC), and mature DC (mDC) from human peripheral blood monocytes (PBMC) obtained from HLA-A2 healthy donors, and pulsed them with human papillomavirus E7 peptide (p11-20), a class I HLA-A2 binding antigen. We then characterized DCs for cell surface phenotype and gene expression profile by microarray technology. We identified a set of 59 genes that distinguished three differentiation stages of DCs (piDC, iDC and mDC). When piDC, iDC and mDC were pulsed with E7 peptide for 2 hrs, the surface phenotype did not change, however, iDCs rather than mDCs showed transcriptional response by up-regulation of a set of genes. A total of 52 genes were modulated in iDC upon antigen pulsing. Elongation of pulse time for iDCs to 10 and 24 hrs did not significantly bring further changes in gene expression. The E7 peptide up-modulated immune response (KPNA7, IGSF6, NCR3, TREM2, TUBAL3, IL8, NFKBIA), pro-apoptosis (BTG1, SEMA6A, IGFBP3 and SRGN), anti-apoptosis (NFKBIA), DNA repair (MRPS11, RAD21, TXNRD1), and cell adhesion and cell migration genes (EPHA1, PGF, IL8 and CYR61) in iDCs. We confirmed our results by Q-PCR analysis. The E7 peptide but not control peptide (PADRE) induced up-regulation of NFKB1A gene only in HLA-A2 positive iDCs and not in HLA-A2 negative iDCs. These results suggest that E7 up-regulation of genes is specific and HLA restricted and that these genes may represent markers of antigen presentation and help rapidly assess the quality of dendritic cells prior to administration to the host.